The description of Alloxysta chinensis, a new Charipinae species from China (Hymenoptera, Figitidae) - Fülöp, Dávid; Mikó, István; Seltmann, Katja; Pénzes, Zsolt; Melika, George (Zootaxa, 2013)
A new figitid species, Alloxysta chinensis Fülöp & Mikó sp nova, based on females, is described from China and South Korea. The functional morphology and the phylogenetic implication of some anatomical structures frequently used in Charipinae and the validity of the genus Carvercharips is discussed. This manuscript is the first of its kind linking descriptive terminology to Hymenoptera Anatomy Ontology classes, which provides persistent links to definitions for terms used within this manuscript.